Saturday

April 19, 2014

April 19, 2014

Posted by **mary** on Sunday, March 7, 2010 at 2:32am.

- 12th grade -
**Reiny**, Sunday, March 7, 2010 at 7:48am12th grade ????

http://www.google.ca/search?hl=en&source=hp&q=-3%284-9%29%2B6-2%28-8%2B5%29&btnI=I%27m+Feeling+Lucky&meta=&aq=f&oq=

-3(4-9)+6-2(-8+5)

= -3(-5) + 6 - 2(-3)

= 15 + 6 + 6

= 27

- 12th grade math -
**drwls**, Sunday, March 7, 2010 at 7:49am(-3*-5) + 6 -2(-3)

= 15 +6 +6 = 27

I have assumed that +6 is a separate added term and not part of (6-2), since there are no parentheses around "6-2"

With parentheses there, the answer would be very different.

**Related Questions**

12th grade - factor completely x^4-16=0

12th Grade Maths - simplify (e is positive) (24e)^1/3 / (3e)^1/3

12th Grade Maths - simplify (e is positive) (24e)^1/3 / (3e)^1/3

12th grade - There are 300 students in 12th grade. What is the total population ...

Math- Completely confused! - Simplify each expression (where possible) and ...

Algebra - Multiply and simplify completely 1. (x-2y)^3 Simplify 2. 2(-3x^3 y^2)^...

12th Grade Vocabulary Antonyms Practice - Does anyone know of a good place that ...

11th grade - The students of litchfield High school are in grades 9,10,11,12. Of...

Math - Can you show me the work to get these answers also? A.Solve each equation...

Algebra 2 help - Consider the following functions. f(x) = x2 − 3x, g(x...